2020
DOI: 10.1186/s12944-020-01260-4
|View full text |Cite
|
Sign up to set email alerts
|

HDL functions and their interaction in patients with ST elevation myocardial infarction: a case control study

Abstract: Background: Recent studies emphasize the importance of HDL function over HDL cholesterol measurement, as an important risk for cardiovascular diseases (CVD). We compared the HDL function of patients with acute coronary syndrome (ACS) and healthy controls. Methods: We measured cholesterol efflux capacity of HDL using THP-1 macrophages labelled with fluorescently tagged (BODIPY) cholesterol. PON1 activities toward paraoxon and phenyl acetate were assessed by spectrophotometric methods. Results:We recruited 150 A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…More recently, a case-control study analyzed 150 patients with acute coronary syndrome (ACS) and 110 healthy adults not presenting clinical CVD and not undergoing any lipid-lowering therapy. In ACS patients, HDL CEC was found to be reduced compared to controls and associated with higher odds of ACS presence, even after adjustment for confounding factors including plasma HDL-C levels [ 64 ]. Interestingly, after 6 months of standard therapy, HDL CEC was restored in ACS patients, further pointing to this functional parameter as a good candidate for CVD risk prediction.…”
Section: Hdl Cec Atherosclerosis and Cardiovascular Riskmentioning
confidence: 99%
“…More recently, a case-control study analyzed 150 patients with acute coronary syndrome (ACS) and 110 healthy adults not presenting clinical CVD and not undergoing any lipid-lowering therapy. In ACS patients, HDL CEC was found to be reduced compared to controls and associated with higher odds of ACS presence, even after adjustment for confounding factors including plasma HDL-C levels [ 64 ]. Interestingly, after 6 months of standard therapy, HDL CEC was restored in ACS patients, further pointing to this functional parameter as a good candidate for CVD risk prediction.…”
Section: Hdl Cec Atherosclerosis and Cardiovascular Riskmentioning
confidence: 99%
“…HDL's capacity to promote cholesterol efflux from macrophages is known to have a strong negative association with the incidence of CVD independent of HDL-C levels [ 19 ], and we have previously demonstrated that low CEC is associated with higher odds of having acute coronary syndrome [ 14 ]. We observed a lower CEC in individuals with obesity than control subjects in concordance with other published studies [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed according to a previously described protocol [ 10 , 14 , 15 ]. The serum samples were treated with 20% polyethylene glycol as the precipitating reagent to isolate apo B depleted serum.…”
Section: Methodsmentioning
confidence: 99%
“…43 Indeed, the role of HDL-c in the removal of fats and cholesterol from cells within the artery wall atheroma, and the transportation of lipids to the liver for excretion or re-utilization has been linked to acute coronary syndrome. 44 Elevated TG and T. chol levels, on the other hand, have been associated with increased risk of cardiovascular disease, 45 and the increase in risk may be attributed to lipids deposition and arterial obstruction to blood flow.…”
Section: Discussionmentioning
confidence: 99%